Analysis of Changes in Retinal Thickness in Type 2 Diabetes without Diabetic Retinopathy. (25th February 2018) - Jiang, Jing; Liu, Yan; Chen, Yingchao; Ma, Bo; Qian, Yiwen; Zhang, Zhenzhen; Zhu, Dongqing; Wang, Zhiliang; Xu, Xiaofang
Abstract : Objective . To examine the changes in retinal thickness of patients with diabetes without DR. Designs . A randomization, crossover, retrospective practice. Participants . 43 diabetic patients and 43 ethnic-, age-, and sex-matched controls. Methods . Full retinal thicknesses of ten areas were assessed using spectral domain optical coherence tomography. Confounding variables, such as age, gender, and glycated haemoglobin (HbA1c) level, were assessed by regression analysis. Main Outcome Measures . Mean retinal thickness of ten areas. Results . The mean thickness of the fovea was 215.8 ± 18.9  μ m in the diabetes group and 222.0 ± 18.6  μ m in the control group (p = 0.04 ). The mean thickness of the temporal parafovea was 319.9 ± 16.7  μ m in the diabetes group and 326.0 ± 14.4  μ m in the control group (p = 0.01 ). The mean thickness of the temporal perifovea was 276.4 ± 27.9  μ m in the diabetes group and 284.8 ± 17.4  μ m in the control group (p = 0.02 ). There were no significant differences in retinal thickness between groups in other areas (p > 0.05 ). Regression analysis revealed that decreased retinal thickness of the temporal perifovea was associated with a higher HbA1c level (>8.7%) (p = 0.04 ). Conclusion and Relevance . Subtle structural changes in the retina may occur in diabetes without DR. Decreased retinal thickness appeared to begin in the fovea and temporal areas. A high HbA1c level was the main factor influencing retinal thickness.